Industry 4.0 applied to supply chain management: a literature review - Souza, Gabriel Marques de; Abreu, Victor Souza de; D'Agosto, Marcio de Almeida (Brazilian Journal of Production Engineering, 2021)
The development of industry 4.0 is popularizing the new technologies to improve logistics and supply chain management activities to increase process efficiency. Therefore, the present work aims to identify the current research conditions on the subject through a bibliometric and systematic review of papers published on the base Web of Science, giving a special focus to Brazilian studies, that is still in growth. The results show the growing relevance of the theme and the interest on the part of major journals. In relation to the national publications, there is interest in the internet of things and in the cyber-physical systems. The Brazilian analyzed papers focus on economic and operational issues, but there is also a concern about environmental issues.